A Reversible Chemogenetic Switch for Chimeric Antigen Receptor T Cells. Issue 10 (18th January 2022) - Cao, Wenyue; Geng, Zhi Zachary; Wang, Na; Pan, Quan; Guo, Shaodong; Xu, Shiqing; Zhou, Jianfeng; Liu, Wenshe Ray
Abstract: As a revolutionary cancer treatment, the chimeric antigen receptor (CAR) T cell therapy suffers from complications such as cytokine release syndromes and T cell exhaustion. Their mitigation desires controllable activation of CAR‐T cells that is achievable through regulatory display of CARs. By embedding the hepatitis C virus NS3 protease (HCV‐NS3) between the single‐chain variable fragment (scFv) and the hinge domain, we showed that the display of anti‐CD19 scFv on CAR‐T cells was positively correlated to the presence of a clinical HCV‐NS3 inhibitor asunaprevir (ASV). This novel CAR design that allows the display of anti‐CD19 scFv in the presence of ASV and its removal in the absence of ASV creates a practically reversible chemical switch. We demonstrated that the intact CAR on T cells can be repeatedly turned on and off by controlling the presence of ASV in a dose dependent manner both in vitro and in vivo, which enables delicate modulation of CAR‐T activation during cancer treatment. Abstract : Using asunaprevir to control the activity of HCV NS3 protease embedded in a chimeric antigen receptor (CAR) on T cells, the CAR can be repeatedly turned on and off to target tumor cells for their elimination.